Effects of different crops on rhizosphere bacterial diversity under immature soil conditions. Issue 1 (2nd January 2022) - Cao, Xiaoning; Liu, Sichen; Chen, Ling; Wang, Junjie; Xiang, Dabing; Zhang, Jingzhong; Qiao, Zhijun
ABSTRACT: Setaria italica, Panicum miliaceum var. compactum, and Chenopodium quinoa have strong stress resistance, allowing adaptation to poor environments. The study of the stress resistance mechanisms of these crops has important significance for humans. The microbial diversity and metabolic pathways in soil collected from the rhizospheres of S. italica, P.miliaceum var. compactum, and C.quinoa were investigated using high-throughput sequencing. The taxonomic composition analysis of the flora indicates that during seedling and flowering stages, compared with immature soil samples, the main differential genera were Brachybacterium ( p < 0.05), Pimelobacter ( p < 0.05) and Candidatus Nitrososphaera ( p < 0.05) for C. quinoa rhizosphere soil samples; Glycomyces for S. italica rhizosphere soil samples ( p < 0.05); and Pseudomonas for P.miliaceum var. compactum rhizosphere soil samples ( p < 0.05). Functional prediction analysis showed that, in two different samples, the calcium signaling pathway in S. italica soil microbes was enriched. For P.miliaceum var. compactum and C. quinoa, the enriched metabolic pathways were clavulanic acid biosynthesis and biosynthesis of the type II polyketide backbone, respectively (all, p < 0.05). This study indicates that crop species and sampling times have significant effects on the diversity of rhizosphere microorganisms under immature soil conditions.